Analisis Penerapan Manajemen Keuangan Syariah pada Pengelolaan Dana Bantuan Operasional Sekolah (BOS) di Madrasah Ibtidaiyah Negeri 2 Tanjung Jabung Barat - Selviana, Nanda Rahayu; Kurniawan, Bambang; Hamzah, Maulana (Darul Yasin Al Sys, 2024)
Madrasah Ibtidaiyah Negeri 2 Tanjung Jabung Barat is one of the school located in the village with quite a large number of students. As a school that focuses on Islamic religious subjects, school need to understand the principles of sharia financial management in managing School Operational Assistance (BOS) funds in order to avoid problems that can hinder the educational process. Therefore, this research aims to evaluate and analyze the application of sharia financial management in managing BOS funds in school. This research uses qualitative methods with descriptive research type. The data sources used are primary and secondary data. Data collection methods include observation, interviews, documentation, and drawing conclusions. The results of the research show that the implementation of sharia financial management in managing BOS funds at Madrasah Ibtidaiyah Negeri 2 Tanjung Jabung Barat, especially the implementation of planning, organizing, implementing and controlling functions, has been carried out well; However, transparency of information to the committee still needs to be improved. The use of funds needs to be aligned with priority needs for better efficiency, and detailed reporting is not yet fully optimal. Increasing transparency and committee involvement is very important to increase public trust in Madrasah financial governance.